Testing the Effects of a Virtual Reality Game for Aggressive Impulse Management (VR-GAIME): Study Protocol - Smeijers, Danique; Koole, Sander L. (Frontiers in Psychiatry, 2019)
Background: Prior laboratory findings indicate that training avoidance movements to angry faces may lower anger and aggression among healthy participants, especially those high in trait anger. To enrich this training and make it more suitable for clinical applications, it has been developed into a Virtual Reality Game for Aggressive Impulse Management (VR-GAIME). Methods: The proposed study will examine the effects of this training in a randomized controlled trial among forensic psychiatric outpatients with aggression regulation problems (N = 60). In addition to the aggression replacement training, participants will play either the VR-GAIME or a control game. Anger will be assessed using self-report. Aggressive impulses will be measured via self-report, a validated laboratory paradigm, and rated by clinicians. Discussion: The authors hypothesize that the combination of the VR-GAIME and regular aggression treatment will be more successful in reducing aggressive behavior. One of the strengths of the proposed study is that it is the first to examine the effects of a motivational intervention in a clinical sample characterized by problems in regulating anger and aggression. Another strength of the proposed study is that the VR-GAIME will be implemented as a multi-session intervention. Additionally, the VR-GAIME applies, for the first time, serious gaming and virtual reality on an avoidance motivation intervention. If positive results are found, the VR-GAIME may be systematically deployed in forensic psychiatric settings. Trial registration: The trial is registered with The Netherlands National Trial Register, number: NTR6986.